ANALISIS PEMANFAATAN MEDIA ANIMASI DALAM ANIME HATARAKU SAIBO (CELLS AT WORK) SEBAGAI SUMBER BELAJAR BIOLOGI SEL - Muhammad Al Fajri (UNZAH Genggong, 2021)
This study aims to enrich the media and learning resources in Biologyeducation, especially Cell Biology. Therefore, biology teachers are required to be able to answer today's challenges by utilizing interesting media and learning resources. Media and learning resources for biology that can be used are animation media in the anime Hataraku Saibo which is a Japanese animated film series that tells about the daily life of cells in the human body. From the results of the discussion using the descriptive analysis method, it was found that this anime met the criteria to be used as a media and source of learning for cell biology.Keywords: Anime, Hataraku Saibo, Medium and Source for Learning Cell Biology